Infectious Disease Health Problems at Pondok Pesantren X, Pasuruan City in 2023 - Kuuni Ulfah Naila El Muna; Dwi Handayani; Mursyidul Ibad (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2024)
Pesantren is an Islamic educational institution that provides religious education services. Pesantren usually provides dormitories for students, where many people live in one location, resulting in crowded living conditions for an extended period. If anyone who infected an infectous disease which can easily transmit to other, and moreover this can lead to an outbreak which can lead enormous losses. Therefore, we want to do an analysis situation of infectious disease that happened in Pondok Pesantren X. We managed to interview 102 santri and observed some dormitory room. Based on our analysis on the infectious disease situation, we can conclude that the diseases recorded in the clinic do not encompass all illnesses experienced by the students. Common infectious diseases among students in the Pondok Pesantren not only scabies as many people says so, there are also acute respiratory infections, gastroenteritis, typhoid, COVID-19, tuberculosis (TBC), and dengue fever (DBD). We suggest the Caregiver and administrators of the Pondok Pesantren can encourage students to avoid risky behaviors leading to infectious diseases.